Evaluation of the effectiveness of microneedling with tranexamic acid in comparison with microneedling with vitamin C in the treatment of melasma: A prospective and single‐blind clinical trial - Nader Pazyar; Maryam Raeispour; Reza Yaghoobi; Maryam Seyedtabib (Health Science Reports, 2023)
Abstract Background and Aims Melasma is a common skin condition. Microneedling acts as a dermal delivery system that facilitates the penetration of lightening agents such as vitamin C and tranexamic acid (TXA) into the deeper layers of the skin. Therefore, this study aimed to compare the effectiveness of microneedling with TXA with microneedling and vitamin C in treating melasma. Methods In patients with melasma, microneedling was performed at 2–3 mm depth. During that, TXA and vitamin C were poured on the skin of each side of the face, and then each ampoule was soaked for 15 min. This method was performed three times in 2‐week intervals, and the results were compared by measuring the Melasma Area and Severity Index (MASI) score before, during, and 2 months after the completion of the treatment. Results The average MASI score in the baseline in the TXA group was 4.61, and in the vitamin C group was 4.58. The average MASI score in the patients treated with TXA in the last treatment session was 2.40, and the group treated with vitamin C was 2.44. The study results showed that the treatment was effective in both groups based on MASI score. Although there was a difference between the responses of the two groups, it was not significant. Conclusion Microneedling with vitamin C and TXA is a safe and effective treatment option without side effects for treating melasma.